Aggressive Natural Killer Cell Leukemia in an Adolescent Patient: A Case Report and Literature Review - Rong Yang (Frontiers in Pediatrics, 2022)
Aggressive natural killer cell leukemia (ANKL) is a rare malignant tumor, especially uncommon in children. ANKL has very aggressive clinical course and bad prognosis and is usually caused by Epstein-Barr virus infection. ANKL often has clinical manifestations of hemophagocytic lymphohistiocytosis (HLH) and can be easily treated as HLH, which might complicate this aggressive disease. Here we report an ANKL in adolescent whose clinical presentation was highly aggressive and response to L-asparaginase containing chemotherapy was very bad. Early-onset Flow cytometry of peripheral blood and bone marrow help make the diagnosis.